A experiência perceptual na perspectiva da teoria da percepção direta - Broens, Mariana C [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2017)
The objective of this paper is to analyse the concept of skilful action underlying the studies of perceptual experience, especially the visual one, from the perspective of the theory of direct perception. The problem we propose to investigate can be formulated as follows: what are the possible contributions of the concept of affordance to understand the nature of skilful actions generally attributed to processes resulting from internal representations or mental models? In particular, we will try to investigate to what extent the concept of social affordance (as a possibility of action that the bodies of the organisms offer directly to other organisms) can help to understand aspects of complex skilful actions that involve capacities considered as deriving from the possession of a Theory of Mind. We will try to show that the perspective of the ecological psychology of direct perception (Gibson 1986, Turvey 1992, Petrusz & Turvey 2010) allows to understand aspects of human skilled action, especially of a collaborative nature, from a conception of perceptual experience that involves information intrinsically significant.
Perceptual experience from the perspective of the theory of direct perception
Keywords: Affordance; Complex skills; cooperative action.; Experience; Mutuality; Theory of perception/action